MENINGKATKAN PENGAYAAN KOSAKATA PADA PEMBELAJARAN DESCRIPTIVE TEXT MELALUI PENERAPAN MEDIA BELAJAR BERBASIS GAME EDUCANDY PADA KELAS VIRTUAL DI MASA PANDEMI PADA SISWA KELAS X OTKP1 SMK KARTIKA X-2 JAKARTA TAHUN PELAJARAN 2020/2021 - Hikmah, Lu’lu Mamluatul (Jurnal Analisis Pendidikan Sosial, 2025)
This research aims to improve vocabulary enrichment in Descriptive Text material by applying Educandy as a game-based learning media in virtual classroom during the pandemic. This research is a Classroom Action Research (CAR) or known as Penelitian Tindakan Kelas (PTK) that contains several stager those are Planning, Acting, Observing, and Reflecting. The learning method used in this research is descriptive quantitative. The data collection techniques were students’ observation sheet, questionnaires, and vocabulary tests. The subjects were students of class X OTKP 1 SMK Kartika X-2 Jakarta as many as 29 students. The result of this research proves that applying Educandy as a game-based learning media can increase vocabulary enrichment related to Descriptive Text material, it was proven by the percentage results in the pre-cycle activities were by 37.93%, in the first cycle percentage became to 79.31% and in the second cycle increased by 89.66%.